Environmental variability and fishing effects on artisanal flatfish fisheries along the Portuguese coast - Baptista, Vânia; Blasco, Ignacio Pérez; Bueno-Pardo, Juan; Teodósio, Maria Alexandra; Leitão, Francisco (Frontiers in Marine Science, 2022)
Assessing the effects of fishing activity and environmental variability on fishing species might help to understand their fluctuations and to manage them accordingly. However, despite the increasing number of studies linking fisheries and environmental data, few had a multi-species approach considering flatfish species and different age groups. Therefore, this study aims to determine the effects of environmental and fishing related variables on commercial flatfish species across different regions of the Portuguese coast. For that, sea surface temperature, North Atlantic Oscillation, upwelling index, wind components, river discharges and fishing effort were related to landings per unit effort (LPUE) of five commercial flatfish species (Pleuronectes platessa, Dicologlossa cuneata, Microchirus spp., Solea lascaris, and Solea solea) fished by the artisanal fleet along different regions of Portuguese coast (Northwestern coast, Southwestern coast, and Southern coast), using a multi-model statistical approach from 1989 to 2009. The fishing effort had the same effect along the life cycle and was negatively related with LPUE trends for most of the species. Regarding to environmental variability, during early phases (larval to juvenile – age-group-0) the factors that affected the recruitment, in addition to being related to the physiological needs (e.g., sea surface temperature) of individuals that will trigger growth and survival, were related to larval transport and dispersion from offshore spawning areas to coastal nursery habitats beyond (e.g., wind components and upwelling). For juvenile and young-adult phases (age-groups I and II), the effects of environmental variability appeared to be linked to physiological needs important for growth and maturation (e.g., temperature). Concluding, different effects were observed depending on the region, species, and life-cycle phase. Therefore, these environmental-fishing relationships should be used when managing local fishing resources.